Evaluation of surgical Apgar score in predicting post-laparotomy complications - Shah, Nimish J.; Choudhary, Ram Singh; Jangir, Shish Ram; Patel, Divyang (International Surgery Journal, 2020)
Background: Surgical Apgar score is a simple, objective and economical ten point post-operative prognostic scoring system based on three readily recorded intra operative variables. Aim is to evaluate the applicability and accuracy of the surgical Apgar score in predicting post-operative complications and objectives are to identify patients at risk of developing post-operative complications based on intra-operative data, to study the incidence of post-operative complications and morbidity and mortality in patients undergoing elective and emergency laparotomy. Methods: This was a prospective analytical study carried out at SSG Hospital from November 2018 to October 2019 and achieved sample size was 160 patients. Surgical Apgar score was calculated at the end of the operation from these three parameters: heart rate, mean arterial pressure and expected blood loss. Results: Out of 160 patients, 77 patients were in group 0-5 and complications occurred in 45 patients (58.4%), 54 patients in group 6-7 in which 18 patients (33.3%) suffered a complication and 29 patients in 8-10 surgical Apgar score, rate of complications was 17.3% in category 8-10 Apgar score. Conclusions: Complications are more in low Apgar score patients compared to high Apgar score and in emergency cases compared to elective surgeries, would require more intensive monitoring in the postoperative period.